Quantitative and Qualitative Analysis of Weed Vegetation in Coffee Plantations in Bener Meriah Regency - Farahdiba, Dewi; Baidhawi, Baidhawi; Nasruddin, Nasruddin; Nazirah, Laila; Ismadi, Ismadi (International Journal of Engineering, Science and Information Technology, 2025)
Coffee plants are an essential commodity widely cultivated in Bener Meriah Regency, Aceh Province. This study aims to determine the composition of dominant weed types and weed structures in Arabica coffee plantations in Bener Meriah Regency through weed vegetation analysis. Weed vegetation analysis is carried out in two ways, namely quantitative and qualitative. The research was conducted from November 2023 to March 2024 in 5 sub-districts. Weed sampling was carried out on five location plots per sub-district by placing a square measuring 1 m x 1 m diagonally to analyze the number of weeds, the number of individuals, and abundance. The study's results found 2,408 individuals and 35 species of weeds, namely 28 species of broadleaf weeds, three species of puzzles, three species of grasses, and one species of ferns. Spilanthes paniculata Wall weed. Ex DC or jotang is the most dominant weed, with an absolute density value of 392 (SDR 11.82). The absolute frequency value is dominated by Oxalis debilis or calincing. Meanwhile, the highest absolute dry weight was weeded S. paniculata Wall. Ex DC and A. conyzoides with values of 923.3 and 836.2. The life cycle of weeds showed that eight species (22.85%) had annual life cycles, and 27 species (77.15%) had annual life cycles. Stratification is classified as class 3, with as many as 14 species. Sociability is classified as 4th degree as many as 13 species. All weeds are classified as vitality 1. Meanwhile, the periodicity is only nine weed species that do not have flowers, seeds, and fruits.